AN ANALYSIS OF TRANSLATION PROCEDURES IN NOVEL THE PRINCESS DIARIES BY MEG CABOT - Suci Indah Nurvina; Agus Mustajib; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2024)
Analyzing the translation procedures in the novel The Princess Diaries written by Meg Cabot is the aim of the study. The translator's purpose in translating is to identify and to know amount of translation technique between the Source Language (English) into Target Language (Indonesia). In this study used descriptive analysis. Along with explaining and describing the viewpoint, and also analyzes the research item. The selected data was analyzed by using the concepts of Newmark and other relevant theories. Based on the analysis, nine procedures were found in translation, those were: addition, subtraction, transposition, borrowing, cultural equivalent, descriptive equivalent, omission, deletion or reduction, and modulation. The findings showed that all of the procedures and adjustment were applied in the translation processes. Out of 70 sentences being analyzed, 10 sentences apply additional, 8 sentences apply subtraction, 9 sentences apply transposition, 7 sentences apply omission, deletion or reduction, 17 sentences apply borrowing, 5 sentences apply cultural equivalence, 9 sentences apply descriptive equivalences, and 5 sentences apply modulation.